The Management of the Industry in Soviet Lithuania by the Party Leaders: Punishment of Party Members, the Use of Compromising Information Gathered by the KGB and Informal Ties - Grybkauskas, Saulius (Genocidas ir rezistencija, 2008)
The article deals with two important spheres of the Soviet rule which have been little investigated in historiography. Their existence, besides central planning and centralised decision-making define well the Soviet system. The coercive nature of the system and its inner logic implicated the use of such control levers as the punishment of members of the Communist Party and the importance of using compromising information gathered by the KGB in the “work with the cadres”. The article is also concerned with the origins of corruption and informal ties during Soviet times, which is being widely discussed by the general public. Although informal ties and social connections formed by the functionaries are also characteristic of other political-economic systems, the vague system of inflicting punishment which existed in Soviet time made the heads in the economic sector look for possibilities of establishing close ties with party functionaries. The informal relations between the patron (a party functionary) and the client (heads of enterprises) made partly up for the indefinite situation of the latter, giving them certain ideological security. The inflicting of punishment by the party on its members, the KGB activities and the practice of informal ties in industrial enterprises between 1965 and 1985 are analysed.